The Role of Physical Education in Promoting Cardiovascular Health and Preventing Chronic Diseases - Dr. Jyoti Solanki; Dr. Vivek Solanki (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Cardiovascular diseases and chronic illnesses have become a major health concern globally, with sedentary lifestyles and poor dietary habits contributing to the rise in these conditions. Physical education plays a vital role in promoting cardiovascular health and preventing chronic diseases by encouraging physical activity and healthy lifestyle choices. This paper aims to explore the significance of physical education in addressing these health issues and the various strategies that can be implemented to promote cardiovascular health and prevent chronic diseases through physical education programs.Physical education plays a vital role in promoting cardiovascular health and preventing chronic diseases. By providing opportunities for regular physical activity, developing physical fitness skills, and encouraging a physically active lifestyle, PE can significantly reduce the risk of heart disease, stroke, diabetes, and other chronic conditions. However, challenges such as lack of funding, inadequate teacher training, and limited time allocated for PE must be addressed to ensure effective implementation of PE programs. By implementing evidence-based practices, fostering collaboration between policymakers, educators, and communities, and investing in the future of PE, we can create a healthier and more active society for generations to come.